Artificial Intelligence in Anatomy Education - Elies Fitriani; Hanifah Hanifah; Khoirul Ima; Mahfudz Shiddiq; Miko Dharma Alrasyid; Tjahja Nurrobi (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights Review of the potential use of AI in anatomy education, including any weaknesses or threats associated with integrating AI into anatomy teaching. Recommendations for incorporating AI in anatomy education within medical curricula. ABSTRACT Background: Artificial intelligence (AI) refers to machines capable of performing human tasks and exhibiting intelligent behavior. The application of AI in medical education has increased significantly, especially during the COVID-19 pandemic, as remote teaching became widespread across all medical disciplines, including anatomy. Objective: This narrative review aimed to explore the potential use of AI in anatomy education and to identify any associated weaknesses or threats related to its integration. Material and Method: A systematic literature search was conducted using PubMed and Embase (limited to the past 5 years), and Google Scholar (limited to the past 2 years), employing keywords related to